Increasing the efficiency of the chief architect of the project at the initial stages of construction design with a help of the DAD technology on the example of the agrocomplex. - Chertkov, O.; Petruk, Yu.; Tsehelnyi, V. (Ways to Improve Construction Efficiency, 2018)
There are defined main tasks and responsibilities of the chief architect of the project in the article. There are identified main problems and risks in the implementation of the construction project. The definition of DAD technology is given, there are described advantages from its application in the initial stages of design and the impact on the activity of the chief architect of the project.